Analisis Web Design Quality terhadap Customer Trust melalui E-Satisfaction sebagai Variabel Mediasi - Nurhamidah, Nadiza Septiyani; Ramdan, Asep Muhamad; Saori, Sopyan (Universitas Halu Oleo, 2023)
The research was aimed at determining the mediation’s of electronic satisfaction in the relationship of web design on customer trust. The research method used in the research was descriptive and associative method with a quantitative. The technique of sampling deployed was probability sampling by distributing online questionnaires to as many as 250 to the people of Sukabumi City who use the Sociolla website. The technique of analysis data applied was structural Equation Modeling (SEM) with the help of the AMOS 22 software. The result of the reseacrh indicate that Sociolla web has been successful in building good web design, e-satisfaction and customer trust in the eyes of customers. Web design has a positive and significant towards e-satisfaction which is amounted to 7,412; e-sastifaction has a positive and significant towards customer trust which is amounted to 3,494; and e-satisfaction mediates teh relationship between web design and customer trust which is amounted to 1,060. Therefore, it can be concluded that e-satisfaction acts as a mediator of the relationship between web design and customer trust